MATLAB/Simulink modeling of electric motors operating with harmonics and unbalance - Adrián Bolaño Martínez; Isaac Jimenez Navarro; Vladimir Sousa Santos; Enrique Ciro Quispe; Pablo Daniel Donolo (Institute of Advanced Engineering and Science, 2022)
This paper aims to present a simulation model for the analysis of the operational characteristics of electric motors (EMs). The model was developed on the Simulink platform of the MATLAB program and allows analysis in supply conditions with harmonics and voltage unbalance. The contribution of the model is that it considers the mechanical losses and provides for the study of the effect of each component of the electrical sequence of the harmonics and the voltage unbalance on the electromechanical characteristics of the EM. The model developed was tested in a 37.3 kW EM, operating under four power supply conditions: balanced sinusoidal voltages, balanced non-sinusoidal voltages (i.e., harmonics), unbalanced sinusoidal voltages, and non-sinusoidal unbalanced voltages. The results showed that under the conditions of harmonics and unbalance, the efficiency was reduced by 2%, respectively and that with the combined effects, the efficiency decreased by 4%. The results made it possible to quantify, from the current, voltage, and electrical power values of each sequence, the adverse effects caused by voltage unbalance and harmonics.